Working-Time Mismatch and Mental Health - Steffen Otterbach; Mark Wooden; Yin King Fok (Institute for the Study of Labor (IZA), 2016)
Nationally representative panel survey data for Germany and Australia are used to investigate the impact of working-time mismatches (i.e., differences between actual and desired work hours) on mental health, as measured by the Mental Component Summary Score from the SF-12. Fixed effects and dynamic linear models are estimated, which, together with the longitudinal nature of the data, enable person-specific traits that are time invariant to be controlled for. The incorporation of dynamics also reduces concerns about the potential effects of reverse causation. The results suggest that overemployment (working more hours than desired) has adverse consequences for the mental health of workers in both countries. Underemployment (working fewer hours than desired), however, seems to only be of significance in Australia.
Keywords: I12; J22; 330; Australia; Germany; mental health; Mental Component Summary Score (SF-12); longitudinal data; work hours; working-time mismatch